Experience the World and Natural Language - Vondráček, Miloslav (Bohemica Olomucensia, 2024)
Kořenský's linguistic work makes references to philosophy, logic, mathematics and their methodology. Here is an attempt to look at this work from the perspective of leading philosophers. The text presents a comparison of their ways of seeing the world, their correspondences and differences.
Keywords: holism; structuralism; phenomenology; procedural grammar; emergent grammar; Prague School